Design of Recruitment Vendor Selection System to Meet the Needs of it Resources at Startup Company PT XYZ - Rachmadi, Aditya Yudha; Sjarief, Rizal; Yulianto, Budi (Pelopor Publikasi Akademika, 2025)
In the era of globalization, competition among companies in providing goods and services has become increasingly intense, making organizational success highly dependent on competent human resources. Technology-based startups in Indonesia face challenges in acquiring high-quality IT personnel, leading many to adopt outsourcing as a recruitment solution. PT XYZ, a logistics startup that relies on technology and mobile applications, collaborates with outsourcing vendors to meet its IT workforce needs. However, PT XYZ faces difficulties in selecting high-performing vendors due to the absence of an objective and structured selection system. This study aimed to evaluate the reliability of PT XYZ's vendor recruitment assessment system, analyze the criteria and weights used in selecting recruitment vendors, and design a more objective and accurate vendor selection system. The research employs a mixed-method approach, incorporating descriptive analysis and the Analytical Hierarchy Process (AHP) to determine vendor criteria weights, as well as MPE analysis to design the system. The findings indicated that PT XYZ's current vendor assessment system is unreliable, with an average evaluation score of 1.9. The key criteria for vendor selection included integrity (0.157), cooperation (0.094), quality (0.235), timeliness (0.219), cost (0.244), and resource utilization (0.05). Based on the analysis, this study proposes a more effective vendor recruitment selection system to enhance PT XYZ's efficiency and competitiveness in acquiring IT personnel that align with the company's needs.